Structural analysis of a mini three-axis cnc micro-milling machine with horizontal spindle configuration - Saptaji, Kushendarsyah; Octaviani, M.A.; Yetti, M.; Hadisujoto, B.; Juniasih, Octarina Adiati; Azmir, Azhari
Micro-milling is an attractive manufacturing process due to its capability to fabricate miniaturized products. In recent years, more compact and affordable computer numerical control (CNC) machines are available on the market. However, there are not many small-sized high-precision milling machines, especially to fabricate micro sized products. In addition, most of the CNC micro-milling machines used vertical spindle frame position and yet there are not many studies available on the application of horizontal spindle frame position especially in terms of structural analysis. Therefore, this paper contributes to the study of the development of a mini three-axis CNC micro-milling machine using horizontal spindle frame position. This paper discusses the horizontal spindle frame design decision, the structural analysis using finite element analysis (FEA), the prototype, and the machining experiment. The study was conducted in the following steps: (1) defining the spindle position configuration, (2) designing the frame structure, (3) performing finite element analysis, (4) building the machine, and (5) performing experiments. The FEA results show the structure critical location is at the top of vertical work-piece table and the lowest natural frequency occurred at 295 Hz. The micro-milling experiments were able to produce fine circular shape and rectangle features with good visible surface quality. The smallest feature of around 200 µm can be produced by the machine.